Fast and efficient 18F-labeling by [18F]fluorophenylazocarboxylic esters - Fehler, Stefanie; Maschauer, Simone; Höfling, Sarah; Bartuschat, Amelie; Tschammer, Nuska; Hübner, Harald; Gmeiner, Peter; Prante, Olaf; Heinrich, Markus (Chemistry - A European Journal, 2014)
Introduction of [(18) F]fluoride ion into the aromatic core of phenylazocarboxylic esters was achieved in only 30 seconds, with radiochemical yields of up to 95 % (85(±10) %). For labeling purposes, the resulting (18) F-substituted azoester can be further converted in radical-arylation reactions to give biaryls, or in substitutions at its carbonyl unit to produce azocarboxamides. Copyright © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
UnivIS-Import:2015-04-14:Pub.2014.nat.dchph.lphch.fastan